2002
DOI: 10.1007/s005950200019
|View full text |Cite
|
Sign up to set email alerts
|

Successful Management of a Giant Arteriovenous Fistula with a Combination of Selective Embolization and Excision: Report of a Case

Abstract: We experienced a female patient with a giant arteriovenous fistula in her lumbar region, which was successfully managed by a combination of selective embolization and a subsequent total excision. Embolization of the giant arteriovenous malformation resulted in an immediate decrease in the cardiac output and an increase in systemic vascular resistance. Three days after the embolization, a total resection of the lesion was achieved under general anesthesia, with a minimum amount of blood loss. The large skin def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…The concept of regulating flap, that reconstruction using a free flap controls the recurrence or regrowth after resection of AVM, has been proposed. However, no report has evaluated whether free flaps and other flap types clearly prevent the recurrence or regrowth compared with skin grafts…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of regulating flap, that reconstruction using a free flap controls the recurrence or regrowth after resection of AVM, has been proposed. However, no report has evaluated whether free flaps and other flap types clearly prevent the recurrence or regrowth compared with skin grafts…”
Section: Resultsmentioning
confidence: 99%
“…The concept of regulating flap, 15,16 that reconstruction using a free flap controls the recurrence or regrowth after resection of AVM, has been proposed. However, no report has evaluated whether free flaps and other flap types 17,19,25,28,[38][39][40][41][42][43][44][45][46][47][48][49] clearly prevent the recurrence or regrowth compared with skin grafts. 21,23,[50][51][52] According to the present knowledge about the recurrence or regrowth after resection of AVM, 15,16,39,53 whether AVM can be completely resected is important, and, concerning cases in which complete resection is difficult, it has been reported that the hemodynamics in the residual lesions contributes to the recurrence and regrowth, and that it can be controlled by a flap with rich blood flow.…”
Section: Organizationmentioning
confidence: 99%
“…The concept of a regulating flap, that reconstruction using a free flap controls the recurrence or regrowth after resection of AVM, has been proposed. However, no report has evaluated whether free flaps and other flap types clearly prevent the recurrence or regrowth compared with skin grafts…”
Section: Resultsmentioning
confidence: 99%
“…The concept of a regulating flap, 15,16 that reconstruction using a free flap controls the recurrence or regrowth after resection of AVM, has been proposed. However, no report has evaluated whether free flaps and other flap types 17,19,25,28,[38][39][40][41][42][43][44][45][46][47][48][49] clearly prevent the recurrence or regrowth compared with skin grafts. 21,23,[50][51][52] According to the present knowledge on the recurrence or regrowth after resection of AVM, 15,16,39,53 whether AVM can be completely resected is important, and, concerning cases in which complete resection is difficult, it has been reported that the hemodynamics in the residual lesions contribute to the recurrence and regrowth, and that they can be controlled by a flap with rich blood flow.…”
Section: Methods Organizationmentioning
confidence: 99%
“…The concept of regulating flap [15,16], that reconstruction using a free flap controls the recurrence or regrowth after resection of AVM, has been proposed. However, no report has evaluated whether free flaps and other flap types [17,19,25,28,[38][39][40][41][42][43][44][45][46][47][48][49] clearly prevent the recurrence or regrowth compared with skin grafts [21,23,[50][51][52].…”
Section: Commentsmentioning
confidence: 99%